2019
DOI: 10.3390/antiox8070219
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Protection from UV- and Light-Stress Related to Carotenoid Structures

Abstract: This review summarizes studies of protection against singlet oxygen and radical damage by carotenoids. The main focus is on how substitutions of the carotenoid molecules determine high antioxidant activities such as singlet oxygen quenching and radical scavenging. Applied assays were carried out either in vitro in solvents or with liposomes, and in a few cases with living organisms. In the latter, protection by carotenoids especially of photosynthesis against light- and UV-stress is of major importance, but al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(65 citation statements)
references
References 60 publications
3
62
0
Order By: Relevance
“…However, the previous report demonstrated that the NOD-coding gene ( Cmfhp ) was significantly up-regulated when C. militaris CM01 was treated with light [ 8 ], and the deletion of this gene resulted in enhancing nitric oxide (NO) content and lowering carotenoid content as compared with the wild type. Possibly, the down-regulation of the NOD gene found in our study might indicate the presence of a compensatory mechanism through the function of photo-protective pigment [ 42 ] to cope with the stress response or, in turn, that the light-programming condition did not largely induce the light stress, and the cell acclimatization occurred in contrast to the effect of the light exposure, as previously studied [ 8 ].…”
Section: Resultsmentioning
confidence: 65%
“…However, the previous report demonstrated that the NOD-coding gene ( Cmfhp ) was significantly up-regulated when C. militaris CM01 was treated with light [ 8 ], and the deletion of this gene resulted in enhancing nitric oxide (NO) content and lowering carotenoid content as compared with the wild type. Possibly, the down-regulation of the NOD gene found in our study might indicate the presence of a compensatory mechanism through the function of photo-protective pigment [ 42 ] to cope with the stress response or, in turn, that the light-programming condition did not largely induce the light stress, and the cell acclimatization occurred in contrast to the effect of the light exposure, as previously studied [ 8 ].…”
Section: Resultsmentioning
confidence: 65%
“…They evaluated the role of carotenoids in human chronic diseases characterized by oxidative stress, and reported that the beneficial health effects of carotenoids shown in small-scale studies and in subjects suffering from chronic oxidative stress are not evident in large-scale trials with carotenoid supplements. Finally, as recently evidenced by Sandmann et al [127], carotenoids can play a role as direct antioxidants, by quenching singlet oxygen and peroxide radicals.…”
Section: Exogenous Antioxidantmentioning
confidence: 64%
“…However, all antioxidants are not equivalent. Carotenoid action is based on absorption of UV light and quenching of singlet oxygen [60], polyphenols join light absorption with quenching ROS, and tocopherols are a family of antioxidant molecules especially effective in preventing cell membrane oxidation [61]. Antioxidants such as ascorbate do not have π-electrons and can be easily and rapidly oxidized by atmospheric oxygen, thus losing its efficacy as a photoprotector.…”
Section: Natural Products From Plants Herbs and Marine Organismsmentioning
confidence: 99%